DAUGAVPILS MEDICAL COLLEGE STUDENTS’ START POTENTIAL OF MOTIVES FOR A CHOICE OF THE DOCTORS’S ASSISTANT PROFESSION - Jankovska, Livija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Analyses of the students’ education results reveal their insufficient matching with the necessary skills. That serves as a clear evidence for the need of changes in the study process for designing an innovative education system which corresponds to the urgent demands of the modern health care systems. Modern approaches are focused on the development of cognitive and practical skills and attitudes. Covid-19 conditions highlighted the role of health care specialists’ professional attitudes and importance of promoting them in the medical educational process. In addition, long-term pedagogical experience is a basis to claim that college level students also need an assistance for understanding and accepting learning process and taking an active part in it. One of the main aspects of learning is students' readiness to acquire knowledge, active learning and motivation. That is the main reason to define the students' motives to choose the medical profession.